Strengthening Resilience in U.S. Supply Chains: Risks, Vulnerabilities, and Policy Priorities - Ayangbah, Shirley (Economics and Business Journal (ECBIS), 2024)
In order to increase the resilience of the supply chains in the United States, this paper examines the risks and vulnerabilities that exist in them and suggests policy goals. By employing both numerical data and empirical proof, we pinpoint the primary obstacles endangering the steadiness and effectiveness of supply networks. These risks are exacerbated by elements like globalization, technological changes, and natural calamities. We examine different policy initiatives, such as international cooperation, investment plans, and regulations, and provide recommendations to reduce these vulnerabilities and strengthen the resilience of U.S. supply chains .